2015
DOI: 10.1680/tran.13.00039
|View full text |Cite
|
Sign up to set email alerts
|

Key quality factors at urban interchanges

Abstract: Quality of service should not be overlooked in public transport planning and policy making, as it influences modal shift from car use to more sustainable means. Little research has been conducted on the quality of public transport interchanges from the perspective of current travellers (i.e. perceived quality). This work thus aimed to identify key quality factors at urban interchanges through an exploratory approach (multiple correspondence analysis) that provides novel elements for further investigation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Desiderio ( 2 ) and the Auckland Transport Public Transport Interchange Design Guidelines ( 1 ) provide useful overviews of research in this area. The order of these factors vary: for instance, in the U.S.A. service quality aspects (e.g., connectivity and reliability) and personal safety and security are deemed more important than the physical condition of stops and stations ( 9 ), while Dell’Asin et al ( 7 ) found the opposite for travellers in two European cities.…”
Section: Passenger Needs At Interchanges: Previous Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Desiderio ( 2 ) and the Auckland Transport Public Transport Interchange Design Guidelines ( 1 ) provide useful overviews of research in this area. The order of these factors vary: for instance, in the U.S.A. service quality aspects (e.g., connectivity and reliability) and personal safety and security are deemed more important than the physical condition of stops and stations ( 9 ), while Dell’Asin et al ( 7 ) found the opposite for travellers in two European cities.…”
Section: Passenger Needs At Interchanges: Previous Findingsmentioning
confidence: 99%
“…A review of the literature on passenger needs and satisfaction at public transport interchanges shows that very similar factors are important to passengers the world over. These include transfer waiting time, walking distances, reliable services, comfort and convenience (shelter, seating and facilities), safety and security, information (including wayfinding), and fare integration ( 7 10 ). Desiderio ( 2 ) and the Auckland Transport Public Transport Interchange Design Guidelines ( 1 ) provide useful overviews of research in this area.…”
Section: Passenger Needs At Interchanges: Previous Findingsmentioning
confidence: 99%
“…City centers experience an increase in traffic, which in turn brings associated harmful effects. To counter this, efforts have been made to promote a modal shift to the use of more sustainable transport means, such as walking, the use of bicycles and scooters, as well as traditional public transport [ 4 , 5 , 6 , 7 , 8 ]. Recently, a number of studies that measured a reduction of air pollutants from vehicles in city centers due to the pandemic lockdown were published [ 9 , 10 , 11 , 12 ], which further reinforces the point.…”
Section: Introductionmentioning
confidence: 99%